Dynamics of soil cover state and degradation processes intensity in natural soil zones of the Altai Region - Gennady Morkovkin; Yekaterina Litvinenko; Nina Maksimova (Eurasian Journal of Soil Science, 2013)
It is shown that the agricultural landscapes of the natural soil zones of the Altai Region are subjected to intense anthropogenic impact, and they are in an unstable state. Agricultural use has caused an extensive development of degradation processes, and the resulting indicator of those is the increase of eroded soils areas, dehumification, and the decrease of humus soil horizon thickness. More active wind erosion is revealed in the chestnut soil zone of the dry steppe and in the subzone of southern chernozems of arid steppe; a combined action of wind and water erosion is observed in the subzones of arid, temperate-arid and forest-outlier steppe, and water erosion develops in the zones of central forest-steppe and meadow steppe. The highest intensity of dehumification is observed in arid and temperate-arid steppe, and a greater change rate of soils areas in terms of humus horizon thickness decrease is observed in the chestnut soil zone of dry steppe and in the subzone of southern chernozems of arid steppe.